THE EFFECT OF WORKLOAD, WORK ENVIRONMENT, CARERR DEVELOPMENT ON EMPLOYEE JOB SATISFACTION ON PT. SARI COFFEE INDONESIA, Tbk. - Ryani Dhyan Parashakti; Septiani Juniarti; Nurul Khotimah (Dinasti Publisher, 2019)
This research was conducted to determine the effect of workload, work environment and career development on employee job satisfaction. The object of this research is private employees of PT. Sari Coffee Indonesia, Tbk (Case study of the Store Development and Contarction division). This analysis uses independent variables namely workload, work environment and career development. This research was conducted on 50 respondents using quantitative descriptive methods. Therefore, the data analysis used is statistical analysis in the form of multiple linear regression tests. The results of this study indicate that workload and career development have a positive effect on job satisfaction but partially and simultaneously, the environment on job satisfaction of employees of PT. Sari Coffee Indonesia, Tbk (Case study of the Store Development and Contarction division). This is evidenced from the partial results (t test) shows the significant value of the independent variable, namely the work environment of 0,000 which supports the hypothesis. In the test of Variance Analysis (ANOVA) in the multiple regression equation shows that the F-value is greater than the F-table (F = 38.536> F-table = 2.41) or the Probability Value is smaller than 0.05. The value of the multiple correlation coefficient (R) is 0.846 and R Square (R2) is 0.715. The value of R Square (0.715) means that 69.7% of the contribution of job satisfaction can be explained by the three independent variables namely workload, work environment and career development. Therefore the results of this research test state that there is a positive influence between workload variables, work environment and career development on job satisfaction of employees of PT. Sari Coffee Indonesia, Tbk (Case study of the Store Development and Contarction division).